1994
DOI: 10.1007/bf00182302
|View full text |Cite
|
Sign up to set email alerts
|

Serum caffeine levels after 24 hours of caffeine abstention: observations on clinical patients undergoing myocardial perfusion imaging with dipyridamole or adenosine

Abstract: Although caffeine attenuates the vasodilatation produced by dipyridamole and adenosine, and is therefore contraindicated when these agents are used for myocardial perfusion scintigraphy, caffeine levels in clinical patients undergoing standard imaging protocols have not been studied. Eight-six patients undergoing clinically indicated intravenous dipyridamole (n = 75) or adenosine (n = 11) thallium-201 myocardial perfusion scintigraphy, all of whom reported abstention from products containing caffeine for 24 h,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…ISF and blood were sampled by MN treatment and fingerstick, respectively, in nine healthy adult subjects (table S8) who had abstained from caffeine consumption for 36 hours. Baseline caffeine concentrations in ISF and plasma in all participants were below 0.5 g/ml, consistent with expected values >24 hours after caffeine abstention (34). After consuming a soft drink (Diet Coke) containing 43 mg of caffeine, caffeine concentrations in ISF and plasma increased for ~2 hours and then decayed until the end of the 8-hour study (Fig.…”
Section: Monitoring Systemic Biomarker Pharmacokinetics In Isf and Pl...supporting
confidence: 84%
“…ISF and blood were sampled by MN treatment and fingerstick, respectively, in nine healthy adult subjects (table S8) who had abstained from caffeine consumption for 36 hours. Baseline caffeine concentrations in ISF and plasma in all participants were below 0.5 g/ml, consistent with expected values >24 hours after caffeine abstention (34). After consuming a soft drink (Diet Coke) containing 43 mg of caffeine, caffeine concentrations in ISF and plasma increased for ~2 hours and then decayed until the end of the 8-hour study (Fig.…”
Section: Monitoring Systemic Biomarker Pharmacokinetics In Isf and Pl...supporting
confidence: 84%
“…[ 10 ] Similarly in an observational study, caffeine was found in detectable range in 40% of the participants who were abstained from caffeine products for more than 24 h and no significant difference in thallium-201 redistribution was seen in patients with detectable and undetectable serum caffeine levels. [ 17 ] In another study, a detectable level of caffeine was found in 74% of the participants after 12 h abstinence. [ 18 ] Pakistan is the fifth among the 10 countries with high tea and coffee consumption[ 19 ] and possibility of presence of detectable serum level of caffeine despite 12 h of abstinence needs a local prospective study to validate this assumption.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, caffeine was still present in the blood in 40% of the patients when abstaining from caffeine for 24 hours. 10 This indicates, that despite adherence to current guidelines some patients may have substantial caffeine blood levels which may interfere with myocardial perfusion imaging. Another problem is the lack of any definite clinical sign to conclude that patients were adequately stressed following the injection of adenosine receptor agonists.…”
Section: See Related Article Pp 1888-1897mentioning
confidence: 99%